Tree-induced deformation in unsaturated soils - Mu'azu Mohammed Abdullahi; Kamarudin Ahmad; Nazri Ali, supervisor; Fakulti Kejuruteraan Awam (2011)
Thesis (Ph.D (Civil Engineering)) - Universiti Teknologi Malaysia, 2011